The outcome of ex vivo TIL expansion is highly influenced by spatial heterogeneity of the tumor T-cell repertoire and differences in intrinsic in vitro growth capacity between T-cell clones - Poschke, Isabel; Hassel, Jessica C.; Rodríguez Ehrenfried, Aaron; Lindner, Katharina A. M.; Heras-Murillo, Ignacio; Appel, Lena; Lehmann, Johanna; Lövgren, Tanja; Wickström, Stina L.; Lauenstein, Claudia; Roth, Jasmin; König, Anna-Katharina; et al. (Clinical cancer research, 2020)
Purpose: During our efforts to develop tumor-infiltrating lymphocyte (TIL) therapy to counter the devastating recurrence rate in patients with primary resectable pancreatic ductal adenocarcinoma (PDA), we found that PDA TILs can readily be expanded in vitro and that the majority of resulting TIL cultures show reactivity against the autologous tumor. However, the fraction of tumor-reactive T cells is low. We investigated to which extent this was related to the in vitro expansion. - Experimental Design: We compared the clonal composition of TIL preparations before and after in vitro expansion using T-cell receptor (TCR) deep sequencing. Our findings for PDA were benchmarked to experiments with melanoma TILs. - Results: We found that the TIL TCR repertoire changes dramatically during in vitro expansion, leading to loss of tumor- dominant T-cell clones and overgrowth by newly emerging T-cell clones that are barely detectable in the tumor. These changes are primarily driven by differences in the intrinsic in vitro expansion capacity of T-cell clones. Single-cell experiments showed an association between poor proliferative capacity and expression of markers related to antigen experience and dysfunction. Furthermore, we found that spatial heterogeneity of the TIL repertoire resulted in TCR repertoires that are greatly divergent between TIL cultures derived from distant tumor samples of the same patient. - Conclusions: Culture-induced changes in clonal composition are likely to affect tumor reactivity of TIL preparations. TCR deep sequencing provides important insights into the factors that govern the outcome of in vitro TIL expansion and thereby a path toward optimization of the production of TIL preparations with high therapeutic efficacy.See related commentary by Lozano-Rabella and Gros, p. 4177
Gesehen am 06.10.2020